NURSING STRUCTURAL EMPOWERMENT: A CONCEPT ANALYSIS - Latifah Alenazi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: The concept of empowerment originated from the social sciences in the twentieth century. The concept was adopted in nursing to increase the professional progress of nursing sciences. The concept of empowerment is used in nursing as two constructs: structural and psychological. Objectives: The purpose of this paper is to perform a concept analysis of structural empowerment from a nursing perspective. Methods: Walker and Avant’s method of concept analysis was used Results: Autonomy and influence are considered major attributes of the structural empowerment concept in nursing. The method used for concept analysis provided purposeful clarification of the concept and confirmed the findings of the analysis. Conclusion: Structural empowerment in nursing has contributed positively to nurses, patient care, and organizations. It is linked to better quality effects, patient safety, and work effectiveness. Among leadership, it is associated with enhanced role satisfaction. Both inside and outside of organizational contexts, educational programs should play a part in developing empowerment since empowered nurses are more inclined to exercise skills like decision-making, problem-solving, and caregiving. Entail instructional programs to foster critical thinking, leadership, and better comprehension of nursing.